D’un musée de collectionneur à un musée historico-artistique, la collection et la muséographie du Museo Napoleonico de Rome de 1927 à nos jours - Lena-Maria Perfettini (Les Cahiers de l'École du Louvre)
Born in 1927 of the bringing together of the collections of Napoleonic works of art and objects belonging to the brothers Giuseppe and Luigi Primoli, the Museo Napoleonico has had a rich and eventful history: extensions of its premises, expansion of its collection and changes in management. Although it was planned to become a museum dedicated to the private lives of the Bonapartes having lived in Rome, it was used as a propaganda tool by the Fascist regime, which saw the institution as a means of affirming the greatness of Italy. Then it experienced a fall in interest before modernising and being considered a historical-art museum. Thus it gradually distanced itself from the usual definition of a collector’s museum.